Tipografia São Francisco/Lira Nordestina: Práticas culturais, discurso e memória - Freire, Rosangela Vieira (2012)
This research presents a history of the São Francisco Typography constructed in lights of orality studies and the dialogic conception of the language postulated by Mikhail Bakhtin, possessing as main objective to compound an oral history of this printer in its inicial days during the decade of 30, up to its conversion in a cultural point in 2005, bringing the subjects to the scene, giving them voices. In this research, we worked with a corpus formed by verbal and non verbal elements: recorded transcriptions and xilographic printings. The research makes na aproach about folhetos , verifying its relationship with other oral systems, describes the process of xylographic printing since the ilustration of the folhetos covers until the dialog with other suports and makes evident men and women very identified with these productions. As a methodology, we went through interviews, audiovisual documents, photographies, notes and xilographic printings. As partial result, we identified people that acquire folhetos memorize them, we also verifyed a great number of xylographic printing and gethered the reporto of experiences so as to show that we work with live culture.